نظرة الخليفة العباسي -المأمون بن هارون الرشيد-الى الأديان والمذاهب في دولته - كيوان ازاد, أنور (جامعة الوادي - University of Eloued, 2019)
(Abdullah al-Ma'mun Ibn Haron al-Rashid) is considered to be the first Abbasid Caliphate to open up to the religions and doctrines of his state. Some historical sources pointed out that he was inclined to Persians sometimes and then to the Alawites sometimes and tends to the Sunnis and the community a third time, was able to combine this policy contradictory positions and satisfy all parties and overcome most of the difficulties in his time. In order to get to the roots of this policy and the most important reasons that led to dealing with this political, we have prepared this research in two subjects, in order to shed light on some of the features of Islamic civilization in the first Abbasid era in general and the era of Caliph Abdullah, (198-218H/813- 833A.C). He has taken a new path in dealing with the religions and doctrines of his time, and has given way to followers and followers of those religions and sects to perform religious rites and rituals throughout his kingdom freely. On Tuesday, he set up a debate for scholars of these religions and sects. This was not his view of all religions and doctrines, but many of them were similar to the religions (Jews, Christian, Zoroastrian, etc) and the Islamic sects (Sunnis, Shia, Khawarij, Almutazila), while his view of the Mosaic and Mazadak was hostile, Evidence of this fight against the movement of (Babak Al-Kharami) since the outbreak of the year (201H/816A.C) until his death, because it is a busy movement. So that he recommended his brother (Mu'tasim Billah) to fight those apostates of religion and the state and the total elimination of them. Through our study of this subject, we tried to reach the Caliph's approach also towards his contemporaries of supporters and supporters on the one hand and his enemies on the other, by inventorying and analyzing historical sources and references on this aspect, and God reconciling.
مقال
Keywords: - Abbasid-Islamic civilization-al-Ma'mun Ibn Haron al-Rashid-Abbasid-Caliph